DILEMA ETIS PEKERJA SOSIAL DALAM MENERAPKAN NILAI DAN ETIKA PEKERJAAN SOSIAL TERHADAP PENANGANAN PERKAWINAN ANAK USIA DINI - Evi Melda; Kurniati Kurniati (Jurnal Inovasi Penelitian, 2022)
Social work is a profession that is oriented to help and has the main task in overcoming social problems, one of which is to overcome children's problems. The method used in this study is a qualitative method by describing the implementation of the principles of value and ethics of social workers in dealing with child problems and the ethical dilemmas contained in them. The purpose of this research is expected to provide an overview of practice in the field as an effort to improve the quality of social work stuttering increasingly has adequate competence, both in terms of values and ethics in doing the profession.